Twilight of the Titans : Great Power Decline and Retrenchment - MacDonald, Paul K.; Parent, Joseph M. (Book collections on Project MUSE., 2018)
In this bold new perspective on the United States-China power transition, Paul K. MacDonald and Joseph M. Parent examine all great power transitions since 1870. They find that declining and rising powers have strong incentives to moderate their ...